Optimizing the Role of Business Incubators in Higher Education: A Review of Supporting Factors and Barriers - Arief Yanto Rukmana; Ridma Meltareza; Budi Harto; Oom Komalasari; Nining Harnani (West Science Business and Management, 2023)
This research paper explores the role of business incubators in higher education at a university in West Java, focusing on the review of supporting and barrier factors. The study adopts a mixed-methods approach, combining quantitative surveys and qualitative interviews to gather comprehensive data. The findings highlight the importance of supporting factors such as access to resources, mentoring and expertise, networking opportunities, and funding support. Conversely, barrier factors include lack of funding and resources, limited access to mentoring and expertise, ineffective networking opportunities, institutional and policy constraints, and cultural and societal factors. The study provides valuable insights into optimizing the role of business incubators in higher education, emphasizing the need for adequate resources, effective mentoring, networking opportunities, supportive policies, and a favorable entrepreneurial culture.